Glycidyl methacrylate-compatibilized poly(lactic acid)/hemp hurd biocomposites: Processing, crystallization, and thermo-mechanical response. Issue 2 (February 2018) - Khan, Belas Ahmed; Na, Haining; Chevali, Venkata; Warner, Philip; Zhu, Jin; Wang, Hao
Abstract: Poly(lactic acid)-based biocomposites were developed with hemp hurd ( Cannabis sativa L.) with grafting-based interfacial compatibilization. Poly(lactic acid) was extruded with hemp hurd and glycidyl methacrylate as the polymer/hurd interfacial compatibilizer, and injection molded. Interfacial compatibility between poly(lactic acid) and hemp hurd increased with grafted glycidyl methacrylate in comparison to the non-compatibilized control, as corroborated by scanning electron microscopy fractography and mechanical analysis, which showed increases in the glycidyl methacrylate-grafted 20% (w/w) hemp hurd/poly(lactic acid) biocomposite, retaining 94% of the neat polymer strength, with increases in crystallinity, and showing a range of thermo-mechanical properties desirable for rigid biocomposite applications.